Fabricating niosomal-PEG nanoparticles co-loaded with metformin and silibinin for effective treatment of human lung cancer cells - Salmani-Javan, Elnaz; Jafari-Gharabaghlou, Davoud; Bonabi, Esat; Zarghami, Nosratollah (Frontiers in Oncology, 2023)
Background Despite current therapies, lung cancer remains a global issue and requires the creation of novel treatment methods. Recent research has shown that biguanides such as metformin (MET) and silibinin (SIL) have a potential anticancer effect. As a consequence, the effectiveness of MET and SIL in combination against lung cancer cells was investigated in this study to develop an effective and novel treatment method. Methods Niosomal nanoparticles were synthesized via the thin-film hydration method, and field emission scanning electron microscopy (FE-SEM), Fourier transform infrared (FTIR), atomic force microscopy (AFM), and dynamic light scattering (DLS) techniques were used to evaluate their physico-chemical characteristics. The cytotoxic effects of free and drug-loaded nanoparticles (NPs), as well as their combination, on A549 cells were assessed using the MTT assay. An apoptosis test was used while under the influence of medication to identify the molecular mechanisms behind programmed cell death. With the use of a cell cycle test, it was determined whether pharmaceutical effects caused the cell cycle to stop progressing. Additionally, the qRT-PCR technique was used to evaluate the levels of hTERT, BAX, and BCL-2 gene expression after 48-h medication treatment. Results In the cytotoxicity assay, the growth of A549 lung cancer cells was inhibited by both MET and SIL. Compared to the individual therapies, the combination of MET and SIL dramatically and synergistically decreased the IC50 values of MET and SIL in lung cancer cells. Furthermore, the combination of MET and SIL produced lower IC50 values and a better anti-proliferative effect on A549 lung cancer cells. Real-time PCR results showed that the expression levels of hTERT and BCL-2 were significantly reduced in lung cancer cell lines treated with MET and SIL compared to single treatments (p< 0.001). Conclusion It is anticipated that the use of nano-niosomal-formed MET and SIL would improve lung cancer treatment outcomes and improve the therapeutic efficiency of lung cancer cells.